1987
DOI: 10.1177/0013916587191002
|View full text |Cite
|
Sign up to set email alerts
|

The "Sensed Presence" in Unusual Environments Peter Suedfeld

Abstract: Literature on the reactions of contemporary human beings coping with certain kinds of extreme and unusual environments indicates the occasional experience of another entity appearing to provide help or advice, even when no such entity was in fact present. Sources of such reports reviewed in this article include spirit quests, solitary sailing, polar and mountain explorations, and the traumatic experiences of shipwreck and air-crash survivors in remote and hostile environments. The experience is frequently inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…For example, the notion of “copresence” as an experience of sharing the same space with someone else (Schroeder, ) suggests that this experience may vary along dimensions such as subtle versus vivid, transient versus sustained, and variable versus stable (cf. Suedfeld & Mocellin, ). Similarly, in the nursing literature, mere bodily presence (the nurse is in the same room as the patient) is seen as a lower level type of presence in relation to, for example, the “partial” presence implied by the nurse being in the same room as the patient while focusing on tasks relevant to the patient but not really focusing on the patient (Osterman & Schwartz‐Barcott, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the notion of “copresence” as an experience of sharing the same space with someone else (Schroeder, ) suggests that this experience may vary along dimensions such as subtle versus vivid, transient versus sustained, and variable versus stable (cf. Suedfeld & Mocellin, ). Similarly, in the nursing literature, mere bodily presence (the nurse is in the same room as the patient) is seen as a lower level type of presence in relation to, for example, the “partial” presence implied by the nurse being in the same room as the patient while focusing on tasks relevant to the patient but not really focusing on the patient (Osterman & Schwartz‐Barcott, ).…”
Section: Discussionmentioning
confidence: 99%
“…A third consideration likely to provide a piece of a naturalistic account of experiences of apparitions or ghostly presences is the "sensed presence" in unusual environments reported by Peter Suedfeld and Jane Mocellin in the environmental psychology literature Mocellin 1987, Mocellin andSuedfeld 1991). It appears that some kinds of extreme or unusual environments produce "the experience of another entity appearing to provide help or advice, even when no such entity was in fact present" (1987,33).…”
Section: Apparitions Ghosts and Presencesmentioning
confidence: 99%
“…Many of these experiences involve "sensed presence" of a loved one, often a sibling or a lost friend. The common environmental factors appear to be of restricted physical and social stimuli: "information from the ambient world is greatly attenuated and attention is refocused to residual and endogenous stimuli [which] could be the origin of the externalized sensed presence" (Suedfeld and Mocellin 1987). While stress is neither necessary nor sufficient for the experience, the experience itself, in providing a sense of security and/or other resources, appears to be associated with successful coping and provides no factual basis for attributing psychopathology.…”
Section: Apparitions Ghosts and Presencesmentioning
confidence: 99%
“…Luhrmann & Morgain (2012) described how participants in a prayer group frequently described the experience of a ‘near tangible presence’, and Luhrmann’s ethnographic work (summarised in Luhrmann, 2012) has noted how this experience forms an essential component of evangelical religious practice. Suedfeld & Mocellin (1987) described the role of intense physiological states in ‘spirit quests’ common in many traditional religious practices that specifically induce a sensed presence experience, and Granqvist et al (2005) and Granqvist & Larsson (2006) have demonstrated experimentally that the experience can be induced by priming participants with religious concepts.…”
Section: Introductionmentioning
confidence: 99%
“…These include sleep-related hallucinations and paralysis, where it is typically associated with fear and anxiety (Cheyne, Newby-Clark & Rueffer, 1999), epileptic seizure (Landtblom, 2006) and particularly temporal lobe epilepsy (Trimble & Freeman, 2006), psychoactive drug use (Barbosa, Giglio & Dalgalarrondo, 2005), and direct brain stimulation (Arzy & Schurr, 2016); and has been associated with psychosis and auditory hallucinations (Woods et al, 2015), acquired brain injury (Brugger, Regard & Landis, 1996), Parkinson’s disease (Fénelon et al, 2011), and a range of intense emotional or physiological states (Suedfeld & Mocellin, 1987) including bereavement (Steffen & Coyle, 2011). …”
Section: Introductionmentioning
confidence: 99%